142 Cardiac resynchronisation therapy: are two left ventricular leads better than one?. (22nd September 2015) - Ginks, M R; Duckett, S; Hamid, S; Shetty, A; Bostock, J; Razavi, R; Rinaldi, C A
Abstract : Introduction: Cardiac Resynchronisation Therapy (CRT) has revolutionised the treatment of patients with heart failure. However, there remains a significant proportion of patients who do not derive clear clinical benefit. One approach to address this problem is the use of two left ventricular (LV) leads. Intuitively, this may better correct dyssynchrony in a dilated left ventricle and may confer greater efficacy in pacing around areas of scar. We assessed the acute haemodynamic effect of single site and dual site left ventricular pacing in the CRT patient population. Methods: Seventeen patients fulfilling criteria for CRT were studied. Sixteen were male, nine had an ischaemic heart failure aetiology. Thirteen patients were in sinus rhythm and four were in atrial fibrillation. Mean age was 64±11 yrs, EF 24±6%, NYHA 2.4±0.5, QRS duration 159±28 ms. During the CRT implant, a pressure wire was passed to the LV via the femoral or radial artery. After balloon occlusive coronary sinus (CS) venography, two guide sheaths were positioned to place two leads. One was positioned empirically in the posterolateral branch (LV1) and the second was positioned in another vein (LV2) which was felt to be the anatomically less preferable position. Lead capture was confirmed and steady state pacing achieved. Three Recordings of mean peak dP/dt max were taken over ≥10 s each in intrinsic rhythm, with LV pacing in each vein and with combined (dual site) LV pacing at 100 beats per minute. Results: 16/17 (94%) patients had successful placement of two coronary sinus leads. The LV1 lead was placed in the posterolateral vein. The LV2 lead was lateral in four cases, anterolateral in 11, and in the middle cardiac vein in one case. There was one CS dissection during placement of the first LV guide sheath which precluded placement of a second LV lead. Intrinsic mean peak dP/dt was 731±170 mm Hg/s. This improved to 924±228 mm Hg /s with LV1 pacing (p<0.001) and 838±169 mm Hg /s with LV2 pacing (p<0.01 vs intrinsic and LV1). Dual site (LV1+LV2) pacing resulted in mean peak dP/dt of 943±197 mm Hg /s (p<0.001 from intrinsic) and improvement over the less preferred (LV2) position (p<0.001) but was comparable to empirical (LV1) lead position (p=0.33). Conclusions: Empirical posterolateral LV pacing gives similar acute haemodynamic response to dual site LV pacing. Dual site LV pacing confers further acute haemodynamic benefit only in the case of suboptimal LV lead positioning and may represent a therapeutic approach to CRT non-responders.